Autobiografia według alfabetu. Refleksja o "Dwugłosie z życia wziętym" Bożeny Chrząstowskiej i Joanny Ciechanowskiej-Barnuś = An alphabetical autobiography. A reflection on "Dwugłos z życia wzięty" by Bożena Chrząstowska and Joanna Ciechanowska-Barnuś - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Anastazja Seul in the article called "An alphabetical autobiography. A reflection on <<Dwugłos z życia wzięty>> by Bożena Chrząstowska and Joanna Ciechanowskiej-Barnuś" ponders on the autobiography of mother and daughter. The author presents this book written by Polish language teachers to highlight its axiological order.
Keywords: Chrząstowska, Bożena (1929-); autobiografia; porządek aksjologiczny Maxa Schelera; wartości hedonistyczne; wartości witalne; wartości duchowe; wartości sakralne; autobiography; axiological order of Max Scheler; voluptuary values; vital force; spiritual values; sacral values